Gender Differences in Academic Staff Performance: An Advanced Analysis Using PLS-SEM in Higher Education - Ghilan Al-Madhagy Taufiq Hail; Shafiz Affendi Mohd Yusof; Mohanaad Shakir; Maryam Juma Al Farsi; Ibrahim R. Al-Shamsi; Adel Sarea (Emerging Science Journal, 2024)
This study aims to comprehensively explore the intricate dynamics among positive and negative emotions, self-efficacy, and task performance within the unique context of the Covid-19 pandemic in Bahrain, specifically placing emphasis on potential gender-related distinctions within the proposed relationships. The ongoing pandemic accentuates the need to investigate the interplay between emotional states, self-efficacy beliefs, and task performance in academic and teaching domains, especially considering potential gender variations within the framework of a society promoting gender equality. Employing a quantitative survey instrument and rigorous statistical techniques, the study validates its proposed model through indicators such as the coefficient of determination (R²) and predictive relevance (Q²). The diverse sample comprises academic and teaching staff of both genders from Bahrain. Advanced statistical methodologies, including Measurement Invariance (MICOM) and Multigroup Analysis (MGA) facilitated by SmartPLS PLS-SEM, provide deeper insights into gender disparities. Significantly contributing to existing knowledge, this paper elucidates the complex relationships among emotions, self-efficacy, and task performance amid a crisis, with a distinctive focus on meticulously investigating gender differences. The study underscores the consistent positive impact of positive emotions on task performance across genders in Bahrain. Recommendations advocate for prioritizing support for academic and teaching staff during crises, emphasizing the positive impact on academic outcomes. Future research should explore demographic intricacies and potential mediating or moderating factors, deepening the comprehension of these complex dynamics. Highlighting the cascading impact of prioritizing the well-being and morale of academic and teaching staff, the study envisions a positive transformation resonating across various facets of society, extending beyond the confines of academia. Doi: 10.28991/ESJ-2024-SIED1-09 Full Text: PDF